1988
DOI: 10.1163/156853888x00530
|View full text |Cite
|
Sign up to set email alerts
|

Croissance et cycle des voies génitales femelles de Typhlonectes compressicaudus (Duméril et Bibron, 1841), amphibien apode vivipare

Abstract: In Typhlonectes compressicaudus the female genital ducts consist of an oviduct and a uterus. A longitudinal groove runs parallel to the oviduct, instead of a funnel. It's only during the second year after birth that modifications in genital ducts prepare the reproductive cycle. In female adults, funnel and oviduct are provided with cilia as early as October. Glands are developing at the level of the oviduct in which we observe 3 types of cells. After the ovulation (at the end of April), these structures set in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
41
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 0 publications
4
41
0
Order By: Relevance
“…Exbrayat and Sentis (1982) and Exbrayat (1986a) examined the annual testicular cycle of Typhlonectes compressicaudus. De Sa and Berois (1986) described the spermatogenesis of Chthnonerpeton indistinctum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exbrayat and Sentis (1982) and Exbrayat (1986a) examined the annual testicular cycle of Typhlonectes compressicaudus. De Sa and Berois (1986) described the spermatogenesis of Chthnonerpeton indistinctum.…”
Section: Discussionmentioning
confidence: 99%
“…Seshachar (1936) described six stages in male germ cell development: primary spermatogonia, secondary spermatogonia, primary spermatocytes, secondary spermatocytes, spermatids, and sperm in Ichthyophis glutinosus. Exbrayat and Sentis (1982), in their report on the annual reproductive cycle in Typhlonectes compressicauda, identified isogenic series of germ cells as primary spermatogonia, secondary spermatogonia, primary spermatocytes, secondary spermatocytes, spermatids, young sperm, sperm, and free sperm. All these observations are based on a light microscopic perspective.…”
mentioning
confidence: 99%
“…Caecilians (Amphibia: Gymnophiona) are unique among the vertebrates in that they retain the Mullerian duct, the progenitor of the female oviduct, in the adult male as a functional gland, the Mullerian gland (Mü ller, 1831;Tonutti, 1931;Wake, 1970Wake, , 1977aWake, ,b, 1981Exbrayat, 1985Exbrayat, , 1986Exbrayat, , 1992. The Mullerian gland is formed from a large number of tubular glands lined by an epithelium arranged around the circumference of a central Mullerian duct (Wake, 1970(Wake, , 1977a(Wake, ,b, 1981Exbrayat, 1985Exbrayat, , 1986Exbrayat, , 1992.…”
mentioning
confidence: 99%
“…The Mullerian gland is formed from a large number of tubular glands lined by an epithelium arranged around the circumference of a central Mullerian duct (Wake, 1970(Wake, , 1977a(Wake, ,b, 1981Exbrayat, 1985Exbrayat, , 1986Exbrayat, , 1992. We have recently shown that in Uraeotyphlus narayani a distinct duct connects each of the tubular glands to the central Mullerian duct (George et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation